Sustainable Natural Resources and Environmental Issues about Free Trade in the World Trade Organization (WTO) System - Ibrahim Sagio (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The aims of this research is the influence of free trade within the framework of the World Trade Organization-General Agreement on Tariffs and Trade on the environment and natural resources. Nowadays, there are almost no tariff barriers in trade. The research methods used a normative research or library research using qualitative research methods, which does not use statistical measuring instruments. The research results show that the development of globalized trade is due to free trade regulated according to the principles of the General Agreement on Tariff and Trade (GATT)-World Trade Organization (WTO), which encourages free trade aspects with a focus on eliminating barriers to trade, while environmental policy is not as a priority. However, environmental policies are formulated to guarantee the sustainability of trade itself. Typically, environmental pollution stems from the production processes involved in manufacturing goods, the transportation of goods utilizing public infrastructure, and the disposal of waste arising from product packaging or substances that are challenging to decompose naturally. Despite the issuance of environmental policies, these issues often persist without effective resolution.There are only a few countries that have good environmental regulations that can make environmental policies can be effective, which are developed countries that already have Eco-friendly technologies used for environmental control. The efforts that have been made by countries to create a balance between the profits obtained from trade itself and environmental conservation and natural resources are focused on environmental policy at the national level. Countries create environmental standards that are adapted to environmental standards and have been agreed at the international level. Furthermore, various approaches are being implemented to achieve higher environmental standards, through international organizations and multilateral agreements related to preserving the environment and natural resources.